An alkaloid-like 3-azabicyclo[3.3.1]non-3-ene library obtained from the bridged Ritter reaction. Issue 2 (12th January 2017) - Williams, Steven G.; Bhadbhade, Mohan; Bishop, Roger; Ung, Alison T.
Abstract: A small, diverse library of novel alkaloid-like compounds was synthesised using the bridged Ritter reaction with (−)-β-pinene and subsequent scaffold derivatisation. Structural diversity was achieved by varying the nitrile used in the reaction and thus provided an understanding of the influence nitriles have on the reaction outcome; it was determined that more nucleophilic nitriles, gave higher yields. Steric factors also determined the selectivity of scaffold types produced, with larger groups producing predominantly alkene products. X-ray crystallography and attempts to derivatise the imines obtained from the bridged Ritter reaction, highlighted the way the imino nitrogen reacted either not at all or in a stereospecific mannor, due to crowding by adjacent substituents. As the compounds contain either the 3-azabicyclo[3.3.1]nonane or 3-azabicyclo[3.3.1]non-3-ene core architecture, they will also be explored for their biological properties, due to the prevalence of bioactive alkaloids containing these core structures. Graphical abstract: